PROFESSIONAL INTERACTION OF DOCTORS AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM - MOSKALENKO, Olena; MAZURENKO, Olha (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2020)
In the article, on the basis of the analysis of psychological and pedagogical sources, the peculiarities of the professional self-consciousness of medical professionals are revealed. The state of research of the problem of forming the professional consciousness of future medical workers is analyzed. A model of psychological and pedagogical support for the development of professional consciousness of students of higher medical education is offered.